Comparative analysis of hydrometallurgical methods for the recovery of Cu from circuit boards: Optimization using response surface and selection of the best technique by two-step fuzzy AHP-TOPSIS method. (10th March 2020) - Yousefzadeh, Samira; Yaghmaeian, Kamyar; Mahvi, Amir Hossein; Nasseri, Simin; Alavi, Nadali; Nabizadeh, Ramin
Abstract: The present study aims to conduct a comprehensive comparison of five hydrometallurgical processes to recover copper from PCBs by adopting the central composite design. Response surface analysis indicated that temperature is the most critical parameter among all of the leaching processes. The effects of the concentration of leaching agent and reaction time on the efficiency of Cu recovery were also statistically significant. The maximum actual recovery rates of Cu being 90, 88, 82, 72, and 62% were achieved by potassium cyanide (KCN), ethylenediaminetetraacetic acid (EDTA), nitric acid (HNO3 ), ammonium persulfate ((NH4 )2 S2 O8 ), and hydrochloric acid (HCl) under the optimum conditions, respectively. According to the results, potassium cyanide exhibited a more significant potential for Cu recovery than other studied methods. Although the selection of the most appropriate leaching method requires complex decision criteria, this challenge could be overcome using multiple criteria decision making (MCDM) approach. Therefore, a critical comparison of the leaching methods regarding the role of 11 criteria was conducted based on the fuzzy analytic hierarchy process (FAHP) and the technique for order performance by similarity to ideal solution (Fuzzy-TOPSIS). According to the TOPSIS results, the following order can be suggested as the best leaching processes; EDTA > HNO3 > (NH4 )2 S2 O8 > HCl > KCN. Therefore, with regard to the role of all critical factors, it can be concluded that non-toxic, eco-friendly, and economically attractive processes such as EDTA can be considered as a potential substitution method for high-efficiency cyanide-based processes. Graphical abstract: Image 1 Highlights: Five selected hydrometallurgical processes were assessed for Cu recovery from PCBs. The role of three independent variables on Cu recovery was studied. The maximum Cu recovery achieved for the KCN process with an efficiency of 90.35%. The contributions of other essential criteria were determined by FAHP-TOPSIS. Eco-friendly processes (i.e., EDTA) had higher weights in the FAHP-TOPSIS method.